A positive electrode material based on a carbon-coated chromium oxide with a core-shell structure and a preparation method thereof
Patent Information
- Application Number
- CN202510217202.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-02-26
AI Technical Summary
其二,正极材料一般由活性材料、导电材料、粘结材料混合得到,需要进一步提高氧化铬活性材料与其他物质间的作用,利用导电材料与粘结材料形成的交联网络促进电子转移,从而提高电性能;另外,正极材料中的粘结材料一般存在稳定性较差的缺点,导致粘结性下降,使得电子传输阻力增加,电性能下降,导致电池性能的恶化
[0017] Compared with the prior art, the beneficial effects achieved by the present invention are: (1) A chromium oxide active material is prepared; in view of the defect of poor electron transport of chromium oxide itself, the solution increases the conductivity of the particles by constructing a vertically growing conductive carbon layer on the surface of chromium oxide particles, forming an electronic conductive path; the coating layer on the surface of chromium oxide includes binder, conductive carbon and chromium oxide, which, after sintering, can make the electrical contact between chromium oxide particles uniform, promote the specific capacity of chromium oxide, improve the electronic conductivity of the battery electrode, and realize the high-rate discharge of chromium oxide battery; and the bonding force between chromium oxide and conductive carbon is good.
Smart Images

Figure CN120109172B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery technology, and discloses a cathode material based on a core-shell structure with carbon-coated chromium oxide and its preparation method. Background Technology
[0002] Lithium-ion batteries have high energy density and are widely used in various fields. Introducing chromium oxide into the cathode material of novel lithium-ion batteries can produce high-performance lithium-ion batteries with high discharge voltage platform and no voltage hysteresis at low and medium rates.
[0003] In existing technologies, novel lithium-ion battery cathode materials based on chromium oxide suffer from difficulties in electron transport. Further improvements in the electrical performance of these cathode materials are needed to develop chromium oxide-based lithium-ion batteries with high discharge capacity, high rate performance, and high stability. Firstly, it is necessary to effectively improve the conductivity pathway when chromium oxide is used as an active material to promote the full utilization of its capacity. Secondly, cathode materials are generally composed of a mixture of active materials, conductive materials, and binder materials. Further improvements are needed in the interaction between the chromium oxide active material and other substances, utilizing the cross-linked network formed by the conductive and binder materials to promote electron transfer and thus improve electrical performance. Additionally, binder materials in cathode materials generally suffer from poor stability, leading to decreased adhesion, increased electron transport resistance, and decreased electrical performance, ultimately resulting in deterioration of battery performance.
[0004] In summary, addressing the aforementioned issues and developing a high-energy-density, high-stability cathode material based on core-shell structured carbon-coated chromium oxide and its preparation method is of great significance. Summary of the Invention
[0005] The purpose of this invention is to provide a cathode material based on a core-shell structure with carbon-coated chromium oxide and its preparation method, so as to solve the problems mentioned in the background art.
[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a method for preparing a cathode material based on a core-shell structure carbon-coated chromium oxide, comprising the following steps: S1: Mix chromium oxide, conductive carbon, and binder evenly; granulate by spraying at 150~160℃; sinter at 190~450℃ for 12~24h to obtain chromium oxide active material; S2: Add the chromium oxide active material, modified conductive material, and composite binder material to the solvent (water-based solvent) in sequence, grind and mix evenly to obtain the positive electrode material.
[0007] In a more optimized manner, the chromium oxide active material comprises the following raw materials, by mass parts: 90-99 parts chromium oxide, 0.1-5 parts conductive carbon, and 1-3 parts binder; the chromium oxide is CrO3 with a D50 of 5-6 μm; the conductive carbon comprises one or more of carbon nanotubes, graphene, carbon fibers, and conductive carbon black; and the binder comprises polyacrylic acid.
[0008] In a more optimized manner, the positive electrode material comprises the following raw materials, by mass parts: 95-97 parts of chromium oxide active material, 2-3 parts of modified conductive material, and 1-3 parts of composite binder material; the composite binder material comprises polyacrylic acid and crosslinking toughening agent in a mass ratio of 1:(0.5-1).
[0009] In a more optimized manner, the preparation of the modified conductive material includes the following steps: Step 1: Mix vinyl borate pinacol ester, methyl acrylate, and N-phenylmaleimide to form an oily monomer; Step 2: Mix acrylic acid and hydroxyethyl acrylate to form an aqueous monomer; Step 3: Take water, sodium 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonate, aqueous monomer, and oily monomer, mix and stir, heat to 80~85℃, add initiator, add double-bonded conductive carbon, polymerize for 4~6 hours, adjust pH to neutral, keep warm for 20~30 minutes, remove solvent, and obtain modified conductive material.
[0010] In a more optimized manner, the modified conductive material comprises the following raw materials, by mass parts: 150-200 parts water, 0.2-0.3 parts sodium 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonate, 13-21 parts aqueous monomer, 8-15 parts oily monomer, 0.1-0.2 parts initiator, and 400-500 parts double-bonded conductive carbon.
[0011] More preferably, the aqueous monomers include acrylic acid and hydroxyethyl acrylate in a mass ratio of (10~15):(3~6); the oily monomers include methyl acrylate, pinacol vinylborate, and N-phenylmaleimide in a mass ratio of (3~6):(2~3):(3~6).
[0012] In a more optimized manner, the preparation of the double-bonded conductive carbon includes the following steps: adding vinyltrimethoxysilane to ethanol and water, stirring at 40~50℃ for 1~2h, adding conductive carbon, stirring at 40~50℃ for 4~6h, filtering to obtain the solid, drying to obtain the double-bonded conductive carbon; the double-bonded conductive carbon includes vinyltrimethoxysilane and conductive carbon in a mass ratio of (1~2):(10~15).
[0013] In a more optimized manner, the preparation of the crosslinking toughening agent includes the following steps: (1) Add pyromellitic dianhydride, stearyl alcohol, and dimethylpyridine to tetrahydrofuran, mix evenly, heat under reflux for 4-6 hours, remove the solvent, and purify to obtain the toughening agent; (2) Take the toughening agent, N,N-dimethylformamide, and butyltriphenylphosphine bromide, heat to 100-110°C, add epichlorohydrin and react for 5-8 hours, and then treat to remove the solvent and unreacted epichlorohydrin to obtain the crosslinking toughening agent.
[0014] More preferably, the toughening agent comprises the following raw materials, in parts by weight: 2-3 parts pyromellitic dianhydride, 5-8 parts stearyl alcohol, 0.1-0.2 parts dimethylpyridine, and 60-80 parts tetrahydrofuran; The crosslinking toughening agent comprises the following raw materials, in parts by weight: 35-40 parts toughening agent, 0.5-1 part butyltriphenylphosphine bromide, and 12-15 parts epichlorohydrin.
[0015] In a more optimized manner, the preparation of the double-bonded conductive carbon includes the following steps: adding 1.5 parts of vinyltrimethoxysilane to 60 parts of ethanol and 40 parts of water, stirring at 50°C for 1 hour, adding 10 parts of conductive carbon, stirring at 50°C for 5 hours, filtering to obtain the solid, drying to obtain the double-bonded conductive carbon.
[0016] In a more optimized manner, the positive electrode material is coated onto the current collector surface, so that the loading (chromium oxide active material, modified conductive material, and composite binder material) is 1.5~2 mg / cm³. 2 The lithium battery positive electrode sheet is obtained by treating it at 120~140℃ for 4~6 hours; the lithium battery positive electrode sheet can be used to prepare lithium batteries.
[0017] Compared with the prior art, the beneficial effects achieved by the present invention are: (1) A chromium oxide active material is prepared; in view of the defect of poor electron transport of chromium oxide itself, the solution increases the conductivity of the particles by constructing a vertically growing conductive carbon layer on the surface of chromium oxide particles, forming an electronic conductive path; the coating layer on the surface of chromium oxide includes binder, conductive carbon and chromium oxide, which, after sintering, can make the electrical contact between chromium oxide particles uniform, promote the specific capacity of chromium oxide, improve the electronic conductivity of the battery electrode, and realize the high-rate discharge of chromium oxide battery; and the bonding force between chromium oxide and conductive carbon is good.
[0018] (2) The active material of chromium oxide is combined with the modified conductive material and the composite binder to form the cathode material; by modifying the conductive material and optimizing the further defined and modified composite binder, the electrical performance and stability of the cathode material are effectively promoted, and the applicability of the new lithium battery cathode material based on chromium oxide is enhanced.
[0019] The modified conductive material involves first modifying the conductive carbon by double bonding, then introducing monomers containing double bonds, and copolymerizing them under the action of an initiator to introduce similar structures, thereby improving the bonding force between the conductive carbon and the composite binder. During the modification, a certain proportion of water-based and oil-based monomers are introduced. Methyl acrylate can improve the flexibility of the polymer, while vinyl borate pinacol ester and N-phenylmaleimide can improve the high temperature resistance, thus improving the stability and durability of the positive electrode. The proportion of oil-based monomers added needs to be controlled. Too little addition will result in an insignificant improvement in high temperature resistance, while too much addition will lead to a decrease in adhesion.
[0020] To further enhance the stability and durability of the cathode material, this invention introduces a crosslinking toughening agent into the composite binder, in addition to the commonly used polyacrylic acid as a binder. This agent uses pyromellitic dianhydride, which has good heat resistance, as a matrix, grafted with stearyl alcohol to improve overall heat resistance and flexibility, thus mitigating the problem of polyacrylic acid easily detaching when used alone. Furthermore, epoxy groups are introduced through epichlorohydrin, allowing it to react with the composite binder and modified conductive material in subsequent steps to form a three-dimensional network with good elasticity, effectively improving battery life. The amount of this crosslinking toughening agent added should not be excessive; excessive addition leads to over-crosslinking and increased brittleness, which negatively impacts performance. Attached Figure Description
[0021] Figure 1 The specific capacity-voltage test curves are for samples from Examples 1 to 5. Detailed Implementation
[0022] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] It should be noted that there are no special restrictions on the manufacturers of the raw materials involved in this invention. Exemplary examples include: carbon nanotubes (AM-C6-067-1, Zhejiang Yamei Nanotechnology Co., Ltd.), conductive carbon black (AM-C1-064-1, Zhejiang Yamei Nanotechnology Co., Ltd.), polyacrylic acid (item number 181285, average Mv~450000, Sigma-Aldrich), pyromellitic dianhydride (CAS: 89-32-7), stearyl alcohol (CAS: 112-92-5), dimethylpyridine (CAS: 108-48-5), tetrahydrofuran (CAS: 109-99-9), N,N-dimethylformamide (CAS: 68-12-2), butyltriphenylphosphine bromide (CAS: 1779-51-7), epichlorohydrin (CAS: 106-89-8), and vinyltrimethoxysilane (CAS: 2768-02-7). ), ethanol (CAS: 64-17-5), sodium 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonate (CAS: 5165-97-9), acrylic acid (CAS: 79-10-7), hydroxyethyl acrylate (CAS: 818-61-1), methyl acrylate (CAS: 96-33-3), vinyl borate pinacol ester (CAS: 75927-49-0), N-phenylmaleimide (CAS: 941-69-5), initiator (sodium persulfate CAS: 7775-27-1); Unless otherwise specified, all figures below are parts by weight or mass ratios. Example 1: Chromium oxide, carbon nanotubes and polyacrylic acid were mixed in a mass ratio of 97:2:1 to obtain a mixture; the mixture was dried at 150°C and granulated, and kept at 400°C for 18 hours to obtain chromium oxide active material.
[0024] Example 2: Chromium oxide, carbon nanotubes and polyacrylic acid were mixed in a mass ratio of 96:2:2 to obtain a mixture; the mixture was dried at 150°C and granulated, and kept at 400°C for 18 hours to obtain chromium oxide active material.
[0025] Example 3: Chromium oxide, conductive carbon black, and polyacrylic acid were mixed in a mass ratio of 97:2:1 to obtain a mixture; the mixture was dried at 150°C and granulated, and then kept at 400°C for 18 hours to obtain chromium oxide active material.
[0026] Example 4 (Comparative example without added conductive carbon): Chromium oxide and polyacrylic acid were mixed at a mass ratio of 99:1 to obtain a mixture; the mixture was dried at 150°C and granulated, and kept at 400°C for 18 hours to obtain chromium oxide active material.
[0027] Example 5 (Comparative example without added conductive carbon): Chromium oxide and polyacrylic acid were mixed at a mass ratio of 98:2 to obtain a mixture; the mixture was dried at 150°C and granulated, and kept at 400°C for 18 hours to obtain chromium oxide active material.
[0028] Performance testing: The active materials prepared in Examples 1-5 were mixed uniformly with chromium oxide active material, carbon nanotubes, and polyacrylic acid in a mass ratio of 96:2:2 to obtain the positive electrode material; the positive electrode material was coated on the surface of the current collector to achieve a loading of 1.6 mg / cm³. 2 The positive electrode of a lithium battery was obtained by treating the sample at 130℃ for 5 hours. The sample was then assembled into a lithium battery using conventional methods, and its performance was tested. See details below. Figure 1 Compared with Table 1; Table 1:
[0029] Based on the chromium oxide active material prepared according to the formulation of Example 1, Examples 6-8 were set up: Example 6: S1: 1.5 parts of vinyltrimethoxysilane were added to 60 parts of ethanol and 40 parts of water, and stirred at 50°C for 1 hour. 10 parts of carbon nanotubes were added, and stirred at 50°C for 5 hours. The solid was filtered and dried to obtain double-bonded conductive carbon. S2: Take 160 parts water, 0.3 parts sodium 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonate, 12 parts acrylic acid, 3 parts hydroxyethyl acrylate, 5 parts methyl acrylate, 2 parts pinacol vinylborate, and 5 parts N-phenylmaleimide. Stir and heat to 82°C. Add 0.1 parts sodium persulfate as an initiator and 480 parts double-bonded conductive carbon. Polymerize for 5 hours, adjust the pH to neutral, keep warm for 30 minutes, remove the solvent, and obtain the modified conductive material. S3: Add 3 parts of pyromellitic dianhydride, 8 parts of stearyl alcohol, and 0.1 parts of 4-dimethylpyridine to 60 parts of tetrahydrofuran, mix well, heat under reflux for 5 hours, remove the solvent, and then purify to obtain the toughening agent. Take 38 parts toughening agent, 50 parts N,N-dimethylformamide, and 0.5 parts butyltriphenylphosphine bromide, heat to 100℃, add 15 parts epichlorohydrin and react for 6 hours, then remove the solvent and unreacted epichlorohydrin to obtain the crosslinking toughening agent. S4: Add 97 parts of active material, 2 parts of modified conductive material, 1 part of polyacrylic acid, and 0.6 parts of crosslinking toughening agent to the solvent, grind and mix evenly to obtain the positive electrode material.
[0030] Example 7: S1: 1.5 parts of vinyltrimethoxysilane were added to 60 parts of ethanol and 40 parts of water, and stirred at 50°C for 1 hour. 10 parts of carbon nanotubes were added, and stirred at 50°C for 5 hours. The solid was filtered and dried to obtain double-bonded conductive carbon. S2: Take 160 parts water, 0.3 parts sodium 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonate, 10 parts acrylic acid, 5 parts hydroxyethyl acrylate, 3 parts methyl acrylate, 2 parts pinacol vinylborate, and 4 parts N-phenylmaleimide. Stir and heat to 82°C. Add 0.1 parts sodium persulfate as an initiator and 480 parts double-bonded conductive carbon. Polymerize for 5 hours, adjust the pH to neutral, keep warm for 30 minutes, remove the solvent, and obtain the modified conductive material. S3: Add 3 parts of pyromellitic dianhydride, 8 parts of stearyl alcohol, and 0.1 parts of 4-dimethylpyridine to 60 parts of tetrahydrofuran, mix well, heat under reflux for 5 hours, remove the solvent, and then purify to obtain the toughening agent. Take 38 parts toughening agent, 50 parts N,N-dimethylformamide, and 0.5 parts butyltriphenylphosphine bromide, heat to 100℃, add 15 parts epichlorohydrin and react for 6 hours, then remove the solvent and unreacted epichlorohydrin to obtain the crosslinking toughening agent. S4: Add 97 parts of active material, 2 parts of modified conductive material, 1 part of polyacrylic acid, and 0.6 parts of crosslinking toughening agent to a solvent, grind and mix to obtain the positive electrode material.
[0031] Example 8: S1: 1.5 parts of vinyltrimethoxysilane were added to 60 parts of ethanol and 40 parts of water, and stirred at 50°C for 1 hour. 10 parts of carbon nanotubes were added, and stirred at 50°C for 5 hours. The solid was filtered and dried to obtain double-bonded conductive carbon. S2: Take 160 parts water, 0.3 parts sodium 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonate, 10 parts acrylic acid, 5 parts hydroxyethyl acrylate, 3 parts methyl acrylate, 2 parts pinacol vinylborate, and 4 parts N-phenylmaleimide. Stir and heat to 82°C. Add 0.1 parts sodium persulfate as an initiator and 480 parts double-bonded conductive carbon. Polymerize for 5 hours, adjust the pH to neutral, keep warm for 30 minutes, remove the solvent, and obtain the modified conductive material. S3: Add 3 parts of pyromellitic dianhydride, 8 parts of stearyl alcohol, and 0.1 parts of 4-dimethylpyridine to 60 parts of tetrahydrofuran, mix well, heat under reflux for 5 hours, remove the solvent, and then purify to obtain the toughening agent. Take 38 parts toughening agent, 50 parts N,N-dimethylformamide, and 0.5 parts butyltriphenylphosphine bromide, heat to 100℃, add 15 parts epichlorohydrin and react for 6 hours, then remove the solvent and unreacted epichlorohydrin to obtain the crosslinking toughening agent. S4: Add 97 parts of active material, 2 parts of modified conductive material, 1 part of polyacrylic acid, and 0.5 parts of crosslinking toughening agent to solvent and grind and mix to obtain positive electrode material.
[0032] Example 9 (a comparative example with a modified conductive material preparation method, the remaining steps are the same as in Example 6): S1: 1.5 parts of vinyltrimethoxysilane were added to 60 parts of ethanol and 40 parts of water, stirred at 50°C for 1 h, 10 parts of carbon nanotubes were added, stirred at 50°C for 5 h, filtered to obtain solid, dried, and double-bonded conductive carbon was obtained. S2: Take 160 parts water, 0.3 parts sodium 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonate, 6 parts acrylic acid, 1 part hydroxyethyl acrylate, 8 parts methyl acrylate, 4 parts pinacol vinylborate, and 5 parts N-phenylmaleimide. Stir and heat to 82°C. Add 0.1 parts sodium persulfate initiator and 480 parts double-bonded conductive carbon. Polymerize for 5 hours, adjust the pH to neutral, keep warm for 30 minutes, remove the solvent, and obtain the modified conductive material. S3: Add 3 parts of pyromellitic dianhydride, 8 parts of stearyl alcohol, and 0.1 parts of 4-dimethylpyridine to 60 parts of tetrahydrofuran, mix well, heat under reflux for 5 hours, remove the solvent, and then purify to obtain the toughening agent. Take 38 parts toughening agent, 50 parts N,N-dimethylformamide, and 0.5 parts butyltriphenylphosphine bromide, heat to 100℃, add 15 parts epichlorohydrin and react for 6 hours, then remove the solvent and unreacted epichlorohydrin to obtain the crosslinking toughening agent. S4: Add 97 parts of active material, 2 parts of modified conductive material, 1 part of polyacrylic acid, and 0.5 parts of crosslinking toughening agent to solvent and grind and mix to obtain positive electrode material.
[0033] Example 10 (a comparative example with different amounts of crosslinking toughening agent, the rest of the steps are the same as in Example 6): S1: Add 1.5 parts of vinyltrimethoxysilane to 60 parts of ethanol and 40 parts of water, stir at 50°C for 1 hour, add 10 parts of carbon nanotubes, stir at 50°C for 5 hours, filter to obtain solid, dry to obtain double-bonded conductive carbon. S2: Take 160 parts water, 0.3 parts sodium 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonate, 12 parts acrylic acid, 3 parts hydroxyethyl acrylate, 5 parts methyl acrylate, 2 parts pinacol vinylborate, and 5 parts N-phenylmaleimide. Stir and heat to 82°C. Add 0.1 parts sodium persulfate as an initiator and 480 parts double-bonded conductive carbon. Polymerize for 5 hours, adjust the pH to neutral, keep warm for 30 minutes, remove the solvent, and obtain the modified conductive material. S3: Add 3 parts of pyromellitic dianhydride, 8 parts of stearyl alcohol, and 0.1 parts of 4-dimethylpyridine to 60 parts of tetrahydrofuran, mix well, heat under reflux for 5 hours, remove the solvent, and then purify to obtain the toughening agent. Take 38 parts toughening agent, 50 parts N,N-dimethylformamide, and 0.5 parts butyltriphenylphosphine bromide, heat to 100℃, add 15 parts epichlorohydrin and react for 6 hours, then remove the solvent and unreacted epichlorohydrin to obtain the crosslinking toughening agent. S4: Add 97 parts of active material, 2 parts of modified conductive material, 1 part of polyacrylic acid, and 1.2 parts of crosslinking toughening agent to solvent and grind and mix to obtain positive electrode material.
[0034] Example 11 (a comparative example with different amounts of crosslinking toughening agent, the rest of the steps are the same as in Example 6): S1: Add 1.5 parts of vinyltrimethoxysilane to 60 parts of ethanol and 40 parts of water, stir at 50°C for 1 h, add 10 parts of carbon nanotubes, stir at 50°C for 5 h, filter to obtain solid, dry to obtain double bonded conductive carbon. S2: Take 160 parts water, 0.3 parts sodium 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonate, 12 parts acrylic acid, 3 parts hydroxyethyl acrylate, 5 parts methyl acrylate, 2 parts pinacol vinylborate, and 5 parts N-phenylmaleimide. Stir and heat to 82°C. Add 0.1 parts sodium persulfate as an initiator and 480 parts double-bonded conductive carbon. Polymerize for 5 hours, adjust the pH to neutral, keep warm for 30 minutes, remove the solvent, and obtain the modified conductive material. S3: Add 3 parts of pyromellitic dianhydride, 8 parts of stearyl alcohol, and 0.1 parts of 4-dimethylpyridine to 60 parts of tetrahydrofuran, mix well, heat under reflux for 5 hours, remove the solvent, and then purify to obtain the toughening agent. Take 38 parts toughening agent, 50 parts N,N-dimethylformamide, and 0.5 parts butyltriphenylphosphine bromide, heat to 100℃, add 15 parts epichlorohydrin and react for 6 hours, then remove the solvent and unreacted epichlorohydrin to obtain the crosslinking toughening agent. S4: Add 97 parts of active material, 2 parts of modified conductive material, 1 part of polyacrylic acid, and 0.3 parts of crosslinking toughening agent to solvent and grind and mix to obtain positive electrode material.
[0035] Performance testing: The positive electrode materials prepared in Examples 6-11 were coated onto the surface of the current collector to achieve a loading of 1.6 mg / cm³. 2 The positive electrode of the lithium battery was obtained by treating it at 130℃ for 5 hours. The lithium battery was then assembled using conventional methods, and its performance was tested using this sample. See Table 2 for details. Table 2:
[0036] As shown in Table 2, the use of modified conductive materials and the introduction of crosslinking toughening agents in the cathode material can further improve the discharge capacity and stability of lithium batteries. In Example 9, the preparation method of the modified conductive material was changed, that is, the ratio of oily monomers and aqueous monomers was changed, which affected the performance. In Examples 10 and 11, the amount of crosslinking toughening agent added was changed, and the performance was not as good as that of Examples 6-8. Therefore, it can be seen that the lithium battery prepared by the cathode material based on the core-shell structure carbon-coated chromium oxide prepared by the present invention has good energy density, high discharge capacity, good stability and long service life.
[0037] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a cathode material based on core-shell structured carbon-coated chromium oxide, characterized in that: Includes the following steps: S1: Mix chromium oxide, conductive carbon, and binder evenly; granulate by spraying at 150~160℃; sinter at 190~450℃ for 12~24h to obtain chromium oxide active material; S2: Chromium oxide active material, modified conductive material, and composite binder are added to the solvent in sequence, and then ground and mixed evenly to obtain the positive electrode material; The preparation of the modified conductive material includes the following steps: Step 1: Mix vinyl borate pinacol ester, methyl acrylate, and N-phenylmaleimide to form an oily monomer; Step 2: Mix acrylic acid and hydroxyethyl acrylate to form an aqueous monomer; Step 3: Take water, sodium 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonate, aqueous monomer, and oil monomer, mix and stir, heat to 80~85℃, add initiator, add double-bonded conductive carbon, polymerize for 4~6 hours, adjust pH to neutral, keep warm for 20~30 minutes, remove solvent, and obtain modified conductive material; The composite bonding material includes polyacrylic acid and crosslinking toughening agent in a mass ratio of 1:(0.5~1); The preparation of the crosslinking toughening agent includes the following steps: (1) Add pyromellitic dianhydride, stearyl alcohol, and dimethylpyridine to tetrahydrofuran, mix evenly, heat under reflux for 4-6 hours, remove the solvent, and purify to obtain the toughening agent; (2) Take the toughening agent, N,N-dimethylformamide, and butyltriphenylphosphine bromide, heat to 100-110°C, add epichlorohydrin and react for 5-8 hours, then remove the solvent and unreacted epichlorohydrin to obtain the crosslinking toughening agent.
2. The method for preparing a cathode material based on a core-shell structured carbon-coated chromium oxide according to claim 1, characterized in that: The chromium oxide active material comprises the following raw materials, by mass: 90-99 parts chromium oxide, 0.1-5 parts conductive carbon, and 1-3 parts binder; the chromium oxide is CrO3 with a D50 of 5-6 μm; the conductive carbon includes one or more of carbon nanotubes, graphene, carbon fibers, and conductive carbon black; and the binder includes polyacrylic acid.
3. The method for preparing a cathode material based on a core-shell structured carbon-coated chromium oxide according to claim 1, characterized in that: The positive electrode material comprises the following raw materials, by mass parts: 95-97 parts of chromium oxide active material, 2-3 parts of modified conductive material, and 1-3 parts of composite binder material.
4. The method for preparing a cathode material based on a core-shell structured carbon-coated chromium oxide according to claim 1, characterized in that: The modified conductive material comprises the following raw materials, by mass parts: 150-200 parts water, 0.2-0.3 parts sodium 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonate, 13-21 parts aqueous monomer, 8-15 parts oily monomer, 0.1-0.2 parts initiator, and 400-500 parts double-bonded conductive carbon.
5. The method for preparing a cathode material based on a core-shell structured carbon-coated chromium oxide according to claim 4, characterized in that: The aqueous monomers include acrylic acid and hydroxyethyl acrylate in a mass ratio of (10~15):(3~6); the oily monomers include methyl acrylate, pinacol vinylborate, and N-phenylmaleimide in a mass ratio of (3~6):(2~3):(3~6).
6. The method for preparing a cathode material based on a core-shell structured carbon-coated chromium oxide according to claim 1, characterized in that: The preparation of the double-bonded conductive carbon includes the following steps: adding vinyltrimethoxysilane to ethanol and water, stirring at 40~50℃ for 1~2h, adding conductive carbon, stirring at 40~50℃ for 4~6h, filtering to obtain solid, drying to obtain double-bonded conductive carbon; the double-bonded conductive carbon includes vinyltrimethoxysilane and conductive carbon in a mass ratio of (1~2):(10~15).
7. The method for preparing a cathode material based on a core-shell structured carbon-coated chromium oxide according to claim 1, characterized in that: The toughening agent comprises the following raw materials, in parts by weight: 2-3 parts pyromellitic dianhydride, 5-8 parts stearyl alcohol, 0.1-0.2 parts dimethylpyridine, and 60-80 parts tetrahydrofuran; The crosslinking toughening agent comprises the following raw materials, in parts by weight: 35-40 parts toughening agent, 0.5-1 part butyltriphenylphosphine bromide, and 12-15 parts epichlorohydrin.
8. The cathode material prepared by the method for preparing a core-shell structured carbon-coated chromium oxide cathode material according to any one of claims 1 to 7.
Citation Information
Patent Citations
Preparation method and application of copper-coated chromium oxide positive electrode
CN112201773A
Lithium secondary battery by use of composite material covered with nano surface as active material of positive polar
CN1416189A